A maze-type multi-level pore structure strontium titanate and its preparation method and application

Through the preparation of the labyrinth multi-stage pore structure strontium titanate, the low activity problem of existing strontium titanate materials in the field of photocatalysis is solved, and the high light utilization rate and photoelectric efficiency are achieved, which is suitable for the practical application needs in the field of photocatalysis.

CN117361612BActive Publication Date: 2025-04-29INSTITUTE OF PROCESS ENGINEERING CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311374360.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2022-12-27
Filing Date
2023-10-23
Publication Date
2025-04-29
Estimated Expiration
2043-10-23

AI Technical Summary

Technical Problem

Existing strontium titanate materials show low photocatalytic activity in the field of photocatalysis, with short photogenerated carrier lifetime, short average diffusion length, and low separation efficiency of photogenerated electron-hole pairs, which is difficult to meet the practical application needs.

Method used

Using the labyrinth multi-stage pore structure strontium titanate and its preparation method, a strontium titanate material with multi-stage pores and controllable crystal surface purity is formed through hydrothermal crystallization reaction and the use of template agents.

Benefits of technology

The light utilization rate and photoelectric efficiency of the material are improved, the photocatalytic activity is enhanced, and the preparation method is green and low-carbon, low-cost, and easy to be used in industrialization.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117361612B_ABST
    Figure CN117361612B_ABST
Patent Text Reader

Abstract

The present invention provides a maze-type multi-level pore structure strontium titanate and a preparation method and application thereof, the preparation method comprising the following steps: (1) mixing a strontium source mixed solution and a titanium source mixed solution, and then performing a hydrothermal crystallization reaction under stirring, and obtaining an intermediate product after solid-liquid separation; (2) washing the intermediate product obtained in step (1), and then drying and roasting in sequence to obtain the maze-type multi-level pore structure strontium titanate. The maze-type multi-level pore structure strontium titanate provided by the present invention has the characteristics of multi-level pores, controllable dominant crystal planes, high purity, etc. in structure, and has the advantages of high light utilization rate and high photoelectric efficiency in performance, and can be applied to the fields of new energy, environmental protection, photocatalysis, photovoltaic power generation, and photocatalytic water splitting for hydrogen production.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application claims the priority right of patent application No. 202211691241.6 (the filing date of the prior application is December 27, 2022, and the name of the invention is A maze-type multi-level pore structure strontium titanate and its preparation method and application). Technical Field

[0002] The invention belongs to the field of photocatalytic nanomaterials, new energy and environment, and relates to a strontium titanate with a multi-level pore structure, in particular to a strontium titanate with a maze-type multi-level pore structure and a preparation method and application thereof. Background Art

[0003] Modern science and technology are developing rapidly, and industrial civilization is constantly changing people's lives, but the global energy shortage and environmental problems that follow are becoming more and more serious. Fossil energy is increasingly scarce, and the contradiction between it as a chemical raw material and an energy raw material is becoming increasingly prominent. The environmental problems that humans need to survive are also becoming increasingly severe. The development of new green, low-carbon, low-energy new energy technologies and environmental protection technologies, such as solar photovoltaic power generation, photolysis of water to produce hydrogen, photolysis of organic matter to treat sewage, and photocatalytic treatment of tail gas pollution have become important forward-looking topics.

[0004] In recent years, a number of research results have shown that perovskite materials exhibit high light absorption and energy conversion efficiency (PCE = output energy / input energy) in the ultraviolet and visible light ranges. 3 ) crystals have a very high photon utilization rate and photoelectric conversion efficiency in the ultraviolet band due to their suitable energy band structure, making them an ideal choice for solar photovoltaic power generation and photocatalytic water splitting to produce hydrogen. As a semiconductor material, strontium titanate is much more efficient than single crystal silicon and TiO 2 Strontium titanate has a higher conduction band potential, more doping modification sites, and high stability, and has attracted widespread attention, and has been extensively studied in the fields of photocatalytic hydrogen production and solar cells. However, strontium titanate materials also have some shortcomings that need to be overcome, such as short lifetime of photogenerated carriers, short average diffusion length, and low separation efficiency of photogenerated electron-hole pairs, which leads to low photocatalytic activity, and its performance is far from meeting the needs of practical applications.

[0005] The structure of strontium titanate materials has a significant impact on their photocatalytic performance. For example, different morphologies, crystal forms, structures, band gaps, specific surface areas, pore sizes, etc. are all of great significance. Different morphologies and structures result in different band gaps, specific surface areas, and pore sizes, which in turn affect the performance of optoelectronic materials, such as the absorption and utilization efficiency of light during the photoelectric conversion process, as well as the generation and diffusion rates of photogenerated electrons, thus affecting their optoelectronic performance.

[0006] Compared with ordinary porous strontium titanate, the labyrinth-type porous structure strontium titanate has a larger specific surface area, pore size and pore volume, and has adjustable pore structure and pore wall properties, so it has more active sites or dominant crystal planes. The more important advantage is that the labyrinth-type porous structure has richer multi-level pores and fewer through holes, which can greatly improve the absorption and utilization efficiency of light, thereby greatly improving its activity and photoelectric properties, and has potential huge utilization value.

[0007] However, looking at the research results at home and abroad, there are few studies on porous strontium titanate, and most of them use organic strontium compounds as raw materials, which have problems such as high cost, organic pollution, and difficulty in controlling structure and performance; the application field of maze-type multi-level pore structure strontium titanate is even blank, and related technology research and development and breakthroughs are urgently needed. Summary of the invention

[0008] In view of the shortcomings of the prior art, the present invention aims to provide a maze-type multi-level pore structure strontium titanate and its preparation method and application. The maze-type multi-level pore structure strontium titanate has structural characteristics such as multi-level pores, controllable crystal planes and high purity.

[0009] To achieve this object, the present invention adopts the following technical solutions:

[0010] In a first aspect, the present invention provides a method for preparing strontium titanate with a maze-type multi-level pore structure, the preparation method comprising the following steps:

[0011] (1) mixing a strontium source mixed solution and a titanium source mixed solution, and then performing a hydrothermal crystallization reaction under stirring, and obtaining an intermediate product after solid-liquid separation;

[0012] (2) Washing the intermediate product obtained in step (1), and then drying and calcining in sequence to obtain the maze-type multi-level porous structure strontium titanate.

[0013] The preparation method of the present invention has the characteristics of being green, low-carbon, low-cost, and easy to control the process, and is easy to realize industrial application.

[0014] As a preferred technical solution of the present invention, the strontium source mixed solution in step (1) is a mixture of a strontium source and the first mixture.

[0015] Preferably, the first mixture comprises a mixture of a first solvent and a template.

[0016] Preferably, the mass percentage content of the template in the first solvent is 4-15wt%, for example, it can be 5wt%, 7wt%, 9wt%, 11wt% or 13wt%, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0017] Preferably, the template comprises any one of tetrapropylammonium hydroxide, urea, methylcellulose, carboxymethylcellulose or hexadecyltrimethylammonium bromide or a combination of at least two thereof, typical but non-limiting combinations include a combination of tetrapropylammonium hydroxide and urea, a combination of tetrapropylammonium hydroxide and methylcellulose, a combination of tetrapropylammonium hydroxide and carboxymethylcellulose, a combination of tetrapropylammonium hydroxide and hexadecyltrimethylammonium bromide, a combination of urea and methylcellulose, a combination of urea and carboxymethylcellulose, a combination of urea and hexadecyltrimethylammonium bromide, a combination of methylcellulose and carboxymethylcellulose, a combination of carboxymethylcellulose and hexadecyltrimethylammonium bromide, a combination of methylcellulose and hexadecyltrimethylammonium bromide, or a combination of methylcellulose, carboxymethylcellulose and hexadecyltrimethylammonium bromide.

[0018] Preferably, the first solvent comprises deionized water and / or an alkaline solution.

[0019] Preferably, the alkaline solution comprises any one of lithium hydroxide solution, sodium hydroxide solution or potassium hydroxide solution or a combination of at least two thereof, and typical but non-limiting combinations include a combination of lithium hydroxide solution and potassium hydroxide solution, a combination of lithium hydroxide solution and sodium hydroxide solution, a combination of potassium hydroxide solution and sodium hydroxide solution, or a combination of lithium hydroxide solution, potassium hydroxide solution and sodium hydroxide solution.

[0020] Preferably, the strontium source comprises strontium hydroxide and / or strontium chloride.

[0021] Preferably, the concentration of the strontium source in the strontium source mixture is 0.1-2 mol / L, for example, 0.1 mol / L, 0.5 mol / L, 1 mol / L, 1.5 mol / L or 2 mol / L, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0022] Preferably, the titanium source mixed solution in step (1) is a mixture of a titanium source and a second mixture.

[0023] Preferably, the second mixture comprises a second solvent or a mixture of a second solvent and a crystal plane modifier.

[0024] Preferably, the mass percentage content of the crystal surface modifier in the second solvent is 5%-12wt%, for example, it can be 6wt%, 8wt%, 10wt% or 12wt%, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0025] Preferably, the crystal plane modifier comprises propylene glycol and / or ethylene glycol.

[0026] The crystal plane regulator of the present invention is used for crystal plane modification and selective regulation of strontium titanate crystals. If the titanium source mixed solution does not contain crystal plane regulation, the morphology of the prepared strontium titanate crystals is a conventional regular hexahedron; when the titanium source mixed solution contains a crystal plane regulator, the morphology of the prepared strontium titanate crystals can be an octahedron with better photoelectric performance.

[0027] Preferably, the second solvent comprises an alkaline solution and / or anhydrous ethanol.

[0028] Preferably, the alkaline solution comprises any one of lithium hydroxide solution, sodium hydroxide solution or potassium hydroxide solution or a combination of at least two thereof, and typical but non-limiting combinations include a combination of lithium hydroxide solution and potassium hydroxide solution, a combination of lithium hydroxide solution and sodium hydroxide solution, a combination of potassium hydroxide solution and sodium hydroxide solution, or a combination of lithium hydroxide solution, potassium hydroxide solution and sodium hydroxide solution.

[0029] Preferably, the titanium source comprises titanium dioxide and / or titanium tetrachloride.

[0030] Preferably, the concentration of the titanium source in the titanium source mixed solution is 0.1-1.5 mol / L, for example, 0.1 mol / L, 0.5 mol / L, 1 mol / L or 1.5 mol / L, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0031] Preferably, the molecular ratio of the strontium source in the strontium source mixture in step (1) to the titanium source in the titanium source mixture is (0.8-1.3):1, for example, it can be 0.8:1, 0.9:1, 1:1, 1.1:1, 1.2:1 or 1.3:1, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0032] In the present invention, the molecular ratio of strontium to titanium is (0.8-1.3):1. If the molecular ratio is too high, the purity of the product will be reduced, and if it is too low, the morphology of the product will be poor.

[0033] Preferably, the hydrothermal crystallization reaction in step (1) also includes a template.

[0034] Preferably, the amount of the template added is 1 to 10 wt% of the mass concentration of the strontium source in the strontium source mixture, for example, it can be 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt% or 10wt%, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0035] Preferably, the stirring speed in step (1) is 50 to 500 r / min, for example, it can be 50 r / min, 100 r / min, 200 r / min, 300 r / min, 400 r / min or 500 r / min, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0036] Preferably, the temperature of the hydrothermal crystallization reaction in step (1) is 100-200°C, for example, 100°C, 120°C, 140°C, 160°C, 180°C or 200°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0037] Preferably, the time of the hydrothermal crystallization reaction in step (1) is 6 to 24 hours, for example, it can be 6 hours, 8 hours, 10 hours, 12 hours, 14 hours, 16 hours, 18 hours, 20 hours, 22 hours or 24 hours, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0038] The temperature of the hydrothermal crystallization reaction of the present invention is 100-200° C. If the temperature is too high, it will lead to excessive pressure, difficulty in operation and increased cost, while if the temperature is too low, it will lead to poor product purity and morphology.

[0039] Preferably, the washing in step (2) is performed 2 to 5 times, for example, 2 times, 3 times, 4 times or 5 times.

[0040] Preferably, the washing liquid in the washing in step (2) comprises deionized water and / or anhydrous ethanol.

[0041] Preferably, the drying temperature in step (2) is 50-90°C, for example, it can be 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C or 90°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0042] Preferably, the calcination temperature in step (2) is 350-650°C, for example, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C or 650°C, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0043] Preferably, the calcination time in step (2) is 0.5 to 3 h, for example, 0.5 h, 0.8 h, 1.1 h, 1.4 h, 1.7 h, 2 h, 2.3 h, 2.6 h or 3 h, but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0044] In the preparation method provided by the present invention, the template agent is removed and the pore structure is formed during the calcination process. If the calcination temperature is too high, the pore structure will be destroyed, while if the calcination temperature is too low, the template agent will be incompletely removed and the pore structure will be imperfect.

[0045] As a preferred technical solution of the present invention, the preparation method comprises the following steps:

[0046] (1) mixing a strontium source mixed solution and a titanium source mixed solution, and then stirring at a temperature of 100 to 200° C. and a speed of 50 to 500 r / min for 6 to 24 hours for a hydrothermal crystallization reaction, and obtaining an intermediate product after solid-liquid separation;

[0047] Wherein, the molecular ratio of the strontium source in the strontium source mixture to the titanium source in the titanium source mixture is (0.8-1.3):1; the concentration of the titanium source in the titanium source mixture is 0.1-1.5 mol / L; the concentration of the strontium source in the strontium source mixture is 0.1-2 mol / L;

[0048] (2) The intermediate product obtained in step (1) is washed 2 to 5 times, and then dried at 50 to 90° C. and calcined at 350 to 650° C. for 0.5 to 3 h to obtain the labyrinth-type multi-level porous structure strontium titanate.

[0049] In a second aspect, the present invention provides a strontium titanate with a maze-like multi-level pore structure, wherein the strontium titanate with a maze-like multi-level pore structure is obtained by the preparation method provided in the first aspect.

[0050] In a third aspect, the present invention provides an application of a maze-type multi-level pore structure strontium titanate obtained by the preparation method provided in the first aspect, wherein the maze-type multi-level pore structure strontium titanate is used in any one of the fields of environmental protection, new energy, photocatalysis, photovoltaic power generation, or photolysis of water to produce hydrogen.

[0051] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0052] Compared with the prior art, the present invention has the following beneficial effects:

[0053] (1) The maze-type multi-level pore structure strontium titanate provided by the present invention has the advantages of multi-level pores, high purity, and controllable potential crystal plane;

[0054] (2) The maze-type multi-level pore structure strontium titanate provided by the present invention has excellent properties such as high light utilization rate and photoelectric efficiency;

[0055] (3) The method for preparing strontium titanate with a maze-type multi-level pore structure provided by the present invention has the characteristics of being green, low-carbon, low-cost, and easy to control the process, and is easy to realize industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0056] Figure 1 This is a SEM electron microscope image of the maze-type multi-level pore structure strontium titanate provided in Example 1 of the present invention;

[0057] Figure 2 This is a graph showing the pore distribution analysis results of strontium titanate with a maze-type multi-level pore structure provided in Example 1 of the present invention;

[0058] Figure 3 is the XRD diagram of the maze-type multi-level pore structure strontium titanate provided in Examples 1-5 of the present invention;

[0059] Figure 4 This is a comparison chart of the absorbance of the maze-type multi-level pore structure strontium titanate sample and the conventional non-porous strontium titanate sample provided in Examples 1-2 of the present invention;

[0060] Figure 5 This is the photocurrent test curve of the maze-type multi-level pore structure strontium titanate provided in Example 1. DETAILED DESCRIPTION

[0061] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0062] Example 1

[0063] This embodiment provides a maze-type multi-level pore structure strontium titanate, and the preparation method of the maze-type multi-level pore structure strontium titanate comprises the following steps:

[0064] (1) mixing a strontium source mixed solution and a titanium source mixed solution, and then performing a hydrothermal crystallization reaction at a temperature of 150° C. and a speed of 300 r / min for 18 hours, and obtaining an intermediate product after solid-liquid separation;

[0065] The strontium source mixed solution is a mixture of strontium hydroxide, tetrapropylammonium hydroxide, hexadecyltrimethylammonium bromide and deionized water, the concentration of strontium hydroxide in the strontium source mixed solution is 0.5 mol / L; the mass percentage content of tetrapropylammonium hydroxide in water is 10 wt%;

[0066] The titanium source mixed solution is a mixture of sodium hydroxide solution, titanium dioxide and propylene glycol, the concentration of titanium dioxide in the titanium source mixed solution is 0.5 mol / L; the mass percentage content of propylene glycol in the sodium hydroxide solution is 10 wt%;

[0067] The molecular ratio of the strontium source in the strontium source mixed solution to the titanium source in the titanium source mixed solution is 1.2:1;

[0068] The hydrothermal crystallization reaction process also includes a template agent, and the amount of the template agent added accounts for 5wt% of the mass concentration of the strontium source in the strontium source mixed solution;

[0069] (2) The intermediate product obtained in step (1) is washed three times with deionized water, and then dried at 60° C. and calcined at 500° C. for 2 h to obtain the maze-type multi-level porous structure strontium titanate.

[0070] The SEM electron microscope image of the maze-type multi-level pore structure strontium titanate is as follows: Figure 1 The pore distribution analysis results are shown in Figure Figure 2 As shown, the XRD pattern is Figure 3 As shown in the absorbance comparison diagram Figure 4 As shown, the photocurrent test curve is as follows Figure 5 shown.

[0071] Example 2

[0072] This embodiment provides a maze-type multi-level pore structure strontium titanate, and the preparation method of the maze-type multi-level pore structure strontium titanate comprises the following steps:

[0073] (1) mixing a strontium source mixed solution and a titanium source mixed solution, and then stirring at 100° C. and 500 r / min for 24 hours for hydrothermal crystallization reaction, and obtaining an intermediate product after solid-liquid separation;

[0074] Wherein, the strontium source mixed solution is a mixture of strontium chloride, methyl cellulose, urea and water, and the concentration of the strontium source in the strontium source mixed solution is 0.1 mol / L;

[0075] The titanium source mixed solution is a mixture of titanium tetrachloride, anhydrous ethanol and propylene glycol, and the concentration of the titanium source in the titanium source mixed solution is 2 mol / L;

[0076] The molecular ratio of the strontium source in the strontium source mixed solution to the titanium source in the titanium source mixed solution is 1.3:1;

[0077] The hydrothermal crystallization reaction process also includes a template agent, and the amount of the template agent added accounts for 1wt% of the mass concentration of the strontium source in the strontium source mixed solution;

[0078] (2) The intermediate product obtained in step (1) is washed twice with anhydrous ethanol, and then dried at 50° C. and calcined at 350° C. for 3 h to obtain the labyrinth-type multi-level porous structure strontium titanate.

[0079] The XRD pattern of the maze-type multi-level pore structure strontium titanate is as follows: Figure 3 As shown in the absorbance comparison diagram Figure 4 shown.

[0080] Example 3

[0081] This embodiment provides a maze-type multi-level pore structure strontium titanate, and the preparation method of the maze-type multi-level pore structure strontium titanate comprises the following steps:

[0082] (1) mixing a strontium source mixed solution and a titanium source mixed solution, and then stirring at 200° C. and 50 r / min for 6 h for hydrothermal crystallization reaction, and obtaining an intermediate product after solid-liquid separation;

[0083] Wherein, the strontium source mixed solution is a mixture of strontium hydroxide, deionized water, carboxymethyl cellulose and tetrapropylammonium hydroxide, and the concentration of the strontium source in the strontium source mixed solution is 2 mol / L;

[0084] The titanium source mixed solution is a mixture of titanium tetrachloride, anhydrous ethanol and ethylene glycol, and the concentration of the titanium source in the titanium source mixed solution is 0.1 mol / L;

[0085] The molecular ratio of the strontium source in the strontium source mixed solution to the titanium source in the titanium source mixed solution is 0.8:1;

[0086] The hydrothermal crystallization reaction process also includes a template agent, and the amount of the template agent added accounts for 10wt% of the mass concentration of the strontium source in the strontium source mixed solution;

[0087] (2) The intermediate product obtained in step (1) is washed 5 times with deionized water, and then dried at 90° C. and calcined at 650° C. for 0.5 h to obtain the labyrinth-type multi-level porous structure strontium titanate.

[0088] The XRD pattern of the maze-type multi-level pore structure strontium titanate is as follows: Figure 3 shown.

[0089] Example 4

[0090] This embodiment provides a maze-type multi-level pore structure strontium titanate. The preparation method of the maze-type multi-level pore structure strontium titanate is different from that of Embodiment 1 only in that:

[0091] In this example, the temperature of the hydrothermal crystallization reaction in step (1) is changed to 80°C.

[0092] The XRD pattern of the maze-type multi-level pore structure strontium titanate is as follows: Figure 3 shown.

[0093] Example 5

[0094] This embodiment provides a maze-type multi-level pore structure strontium titanate. The preparation method of the maze-type multi-level pore structure strontium titanate is different from that of Embodiment 1 only in that:

[0095] In this example, the temperature of the hydrothermal crystallization reaction in step (1) is changed to 220°C.

[0096] The XRD pattern of the maze-type multi-level pore structure strontium titanate is as follows: Figure 3 shown.

[0097] Example 6

[0098] This embodiment provides a maze-type multi-level pore structure strontium titanate. The preparation method of the maze-type multi-level pore structure strontium titanate is different from that of Embodiment 1 only in that:

[0099] In this embodiment, the calcination temperature in step (2) is changed to 300°C.

[0100] Example 7

[0101] This embodiment provides a maze-type multi-level pore structure strontium titanate. The preparation method of the maze-type multi-level pore structure strontium titanate is different from that of Embodiment 1 only in that:

[0102] In this embodiment, the calcination temperature in step (2) is changed to 700°C.

[0103] Example 8

[0104] This embodiment provides a maze-type multi-level pore structure strontium titanate. The preparation method of the maze-type multi-level pore structure strontium titanate is different from that of Embodiment 1 only in that:

[0105] In this embodiment, the molecular ratio of the strontium source in the strontium source mixed solution and the titanium source in the titanium source mixed solution in step (1) is changed to 0.5:1.

[0106] Example 9

[0107] This embodiment provides a maze-type multi-level pore structure strontium titanate. The preparation method of the maze-type multi-level pore structure strontium titanate is different from that of Embodiment 1 only in that:

[0108] In this embodiment, the molecular ratio of the strontium source in the strontium source mixed solution and the titanium source in the titanium source mixed solution in step (1) is changed to 2:1.

[0109] Example 10

[0110] This embodiment provides a maze-type multi-level pore structure strontium titanate. The preparation method of the maze-type multi-level pore structure strontium titanate is different from that of Embodiment 1 only in that:

[0111] In this embodiment, propylene glycol is omitted from the strontium source mixed solution in step (1).

[0112] Comparative Example 1

[0113] This comparative example provides a maze-type multi-level pore structure strontium titanate. The preparation method of the maze-type multi-level pore structure strontium titanate is different from that of Example 1 only in that:

[0114] In this comparative example, the washing process described in step (2) was omitted.

[0115] Comparative Example 2

[0116] This comparative example provides a maze-type multi-level pore structure strontium titanate. The preparation method of the maze-type multi-level pore structure strontium titanate is different from that of Example 1 only in that:

[0117] In this comparative example, the drying process described in step (2) was omitted.

[0118] Comparative Example 3

[0119] This comparative example provides a maze-type multi-level pore structure strontium titanate. The preparation method of the maze-type multi-level pore structure strontium titanate is different from that of Example 1 only in that:

[0120] In this comparative example, the mixed strontium source mixed solution and the titanium source mixed solution in step (1) are changed to: mixed strontium hydroxide, titanium dioxide and a template; wherein the molecular ratio of titanium to strontium is 1.2:1, and the amount of the template added is 5wt% of the titanium source.

[0121] Performance testing:

[0122] The representative samples of strontium titanate with a maze-type multi-level pore structure provided in Examples 1-9 were subjected to structural analysis and performance testing, and the results are as follows.

[0123] (1) Through analysis Figure 1 It can be seen that the maze-type multi-level pore structure strontium titanate provided by the present invention has a maze-type multi-level pore structure, and the morphology is octahedral strontium titanate with more dominant crystal planes (i.e., 110 crystal planes and 111 crystal planes, which have higher photoelectric efficiency than 100 crystal planes); and the maze-type multi-level pore structure strontium titanate has more macropores of 50nm-100nm;

[0124] (2) Through analysis Figure 2 It can be seen that through isothermal adsorption-desorption analysis tests, it was found that the sample has micropores and mesopores of 1.5nm-50nm, and the pore sizes that account for a large proportion are 2.2nm, 3.8nm, 17nm, etc.; it can be seen that the sample has a multi-level pore structure in which multi-sized mesopores, micropores and macropores coexist;

[0125] (3) Through analysis Figure 3 It can be seen that the strontium titanate with a maze-type multi-level pore structure provided in Examples 1-5 of the present invention has no detected impurity peaks and is a high-purity strontium titanate crystal;

[0126] (4) Through analysis Figure 4It can be seen that the UV-visible diffuse reflectance analysis curves of the samples provided in Examples 1 and 2 of the present invention and conventional nonporous strontium titanate samples. By comparison, it can be seen that the absorbance of the samples in Examples 1 and 2 is higher than that of conventional nonporous strontium titanate samples, among which the improvement of the sample in Example 1 in the visible light range is particularly significant, and the absorbance can reach 0.2, which is about 5 times that of conventional nonporous strontium titanate samples, and the absorption rate in the transition zone between visible light and ultraviolet light at about 400nm decreases more slowly; the absorption rate of the sample in Example 2 in the visible light band is improved to 0.1, which is about 2.5 times that of conventional nonporous strontium titanate samples. It can be seen that the samples prepared in Examples 1 and 2 of the present invention have higher absorbance, and thus have better light utilization;

[0127] (5) Through analysis Figure 5 It can be seen that the maze-type multi-level pore structure strontium titanate provided by the present invention exhibits good photogenerated electron ability, responds quickly to light, has stronger photoelectric response ability, can generate high transient photocurrent under light irradiation, and can continuously excite the generation of photocurrent under continuous light irradiation. In addition, the photogenerated electron-hole recombination is slow, and the carrier residence time is long, which is conducive to the transfer of photogenerated electrons to the sample to be catalyzed, and is conducive to the progress of photocatalysis. It can be seen that the sample in Example 1 of the present invention has a high photoelectric efficiency and good photoelectric performance.

[0128] In summary, the maze-type multi-level pore structure strontium titanate provided by the present invention has the characteristics of multi-level pores, controllable high purity of dominant crystal planes, etc. in structure; and has the advantages of high light utilization rate and high photoelectric efficiency in performance.

[0129] The applicant declares that the present invention illustrates the detailed structural features of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed structural features, that is, it does not mean that the present invention must rely on the above-mentioned detailed structural features to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the components selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

[0130] The applicant declares that the present invention illustrates the detailed process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing strontium titanate with a maze-type multi-level pore structure, characterized in that: The preparation method comprises the following steps: (1) mixing a strontium source mixed solution and a titanium source mixed solution, and then performing a hydrothermal crystallization reaction at 100 to 200° C. under stirring, and obtaining an intermediate product after solid-liquid separation; The molecular ratio of the strontium source in the strontium source mixed solution to the titanium source in the titanium source mixed solution is (0.8-1.3):1; The strontium source mixed solution is a mixture of a strontium source and a first mixture, wherein the first mixture includes a mixture of a first solvent and a template; The mass percentage content of the template in the first solvent is 4-15wt%, and the amount of the template added accounts for 5-10wt% of the mass concentration of the strontium source in the strontium source mixed solution; The template agent includes any one or a combination of at least two of tetrapropylammonium hydroxide, urea, methyl cellulose, carboxymethyl cellulose or hexadecyltrimethylammonium bromide; The titanium source mixed solution is a mixture of a titanium source and a second mixture, and the second mixture includes a second solvent or a mixture of a second solvent and a crystal surface modifier; The mass percentage content of the crystal plane modifier in the second solvent is 5%-12wt%; The crystal surface modifier includes propylene glycol and / or ethylene glycol; (2) washing the intermediate product obtained in step (1), and then drying and calcining at 350-650° C. to obtain the maze-type multi-level porous structure strontium titanate; The labyrinth-type multi-level pore structure strontium titanate has a multi-level pore structure in which multi-sized mesopores, micropores and macropores coexist.

2. The preparation method according to claim 1, characterized in that: The first solvent includes deionized water and / or an alkaline solution.

3. The preparation method according to claim 2, characterized in that: The alkaline solution includes any one of a lithium hydroxide solution, a sodium hydroxide solution or a potassium hydroxide solution, or a combination of at least two of them.

4. The preparation method according to claim 1, characterized in that: The strontium source includes strontium hydroxide and / or strontium chloride.

5. The preparation method according to claim 1, characterized in that: The concentration of the strontium source in the strontium source mixed solution is 0.1-2 mol / L.

6. The preparation method according to claim 1, characterized in that: The second solvent includes an alkaline solution and / or anhydrous ethanol.

7. The preparation method according to claim 6, characterized in that: The alkaline solution includes any one of a lithium hydroxide solution, a sodium hydroxide solution or a potassium hydroxide solution, or a combination of at least two of them.

8. The preparation method according to claim 1, characterized in that: The titanium source includes titanium dioxide and / or titanium tetrachloride.

9. The preparation method according to claim 1, characterized in that: The concentration of the titanium source in the titanium source mixed solution is 0.1-1.5 mol / L.

10. The preparation method according to claim 1, characterized in that: The stirring speed in step (1) is 50 to 500 r / min.

11. The preparation method according to claim 1, characterized in that: The hydrothermal crystallization reaction time of step (1) is 6 to 24 hours.

12. The preparation method according to claim 1, characterized in that: The washing times in step (2) are 2 to 5 times.

13. The preparation method according to claim 1, characterized in that: The washing liquid in step (2) comprises deionized water and / or anhydrous ethanol.

14. The preparation method according to claim 1, characterized in that: The drying temperature in step (2) is 50-90°C.

15. The preparation method according to claim 1, characterized in that: The calcination time in step (2) is 0.5 to 3 hours.

16. The preparation method according to claim 1, characterized in that: The preparation method comprises the following steps: (1) mixing a strontium source mixed solution and a titanium source mixed solution, and then stirring at a temperature of 100 to 200° C. and a speed of 50 to 500 r / min for 6 to 24 hours for a hydrothermal crystallization reaction, and obtaining an intermediate product after solid-liquid separation; Wherein, the molecular ratio of the strontium source in the strontium source mixture to the titanium source in the titanium source mixture is (0.8-1.3):1; the concentration of the titanium source in the titanium source mixture is 0.1-1.5 mol / L; the concentration of the strontium source in the strontium source mixture is 0.1-2 mol / L; (2) The intermediate product obtained in step (1) is washed 2 to 5 times, and then dried at 50 to 90° C. and calcined at 350 to 650° C. for 0.5 to 3 h to obtain the labyrinth-type multi-level porous structure strontium titanate.

17. A maze-type multi-level pore structure strontium titanate, characterized in that: The maze-type multi-level pore structure strontium titanate is obtained by the preparation method described in any one of claims 1-16.

18. An application of the maze-type multi-level pore structure strontium titanate as claimed in claim 17, characterized in that: The labyrinth-type multi-level pore structure strontium titanate is used in any one of the fields of environmental protection, new energy, photocatalysis, photovoltaic power generation or photolysis of water to produce hydrogen.